2009
DOI: 10.1093/schbul/sbp023
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Schizophrenia Prevalence to Latitude, Climate, Fish Consumption, Infant Mortality, and Skin Color: A Role for Prenatal Vitamin D Deficiency and Infections?

Abstract: Previous surveys found a large (>10-fold) variation in schizophrenia prevalence at different geographic sites and a tendency for prevalence to increase with latitude. We conducted meta-analyses of prevalence studies to investigate whether these findings pointed to underlying etiologic factors in schizophrenia or were the result of methodological artifacts or the confounding of sites' latitude with level of healthcare at those sites. We found that these patterns were still present after controlling for an index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 79 publications
0
99
1
1
Order By: Relevance
“…While we did not find any differences in S-25 OH D between adult patients with psychotic disorders and healthy controls, prospective studies have suggested vitamin D deficiency as a contributing factor to higher risk of developing psychotic disorders in dark skinned immigrants (McGrath, 1999;Dealberto, 2007;Kinney et al, 2009;McGrath, 2011). There are also associations between vitamin D deficiency and known risk factors for psychotic disorders like urban living, winter births (Kendell and Adams, 2002) and migration (Dealberto, 2007) An important strength of the current study is that the patient sample consists of both in-and outpatients, and thus can be seen as more representative of patients in general compared to samples recruited from inpatients' wards only.…”
Section: Discussioncontrasting
confidence: 85%
“…While we did not find any differences in S-25 OH D between adult patients with psychotic disorders and healthy controls, prospective studies have suggested vitamin D deficiency as a contributing factor to higher risk of developing psychotic disorders in dark skinned immigrants (McGrath, 1999;Dealberto, 2007;Kinney et al, 2009;McGrath, 2011). There are also associations between vitamin D deficiency and known risk factors for psychotic disorders like urban living, winter births (Kendell and Adams, 2002) and migration (Dealberto, 2007) An important strength of the current study is that the patient sample consists of both in-and outpatients, and thus can be seen as more representative of patients in general compared to samples recruited from inpatients' wards only.…”
Section: Discussioncontrasting
confidence: 85%
“…Among 20 articles identified and fully reviewed, 3 were further excluded because they did not meet the criteria for inclusion [11][12][13]. We also excluded a randomized control trial of a fish flour bread spread because of the different nature of the exposure compared to observational studies of seafood intake [14••].…”
Section: Review Strategymentioning
confidence: 99%
“…The prevalence of psychotic disorders varies among different geographical locations, with increased rates in cold climates and high latitudes (Kinney et al, 2009). Furthermore, prevalence increases in individuals born in Winter/Spring months compared to Summer/Autumn babies (Kinney et al, 2009;Saha et al, 2005). These ecological findings suggest sun exposure and therefore vitamin D is a risk factor for psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%